Research Progress on the Mechanism and Management of Septic Cardiomyopathy: A Comprehensive Review - Pei, Xue-Bin; Liu, Bo (Emergency Medicine International, 2023)
Sepsis is defined as a kind of life-threatening organ dysfunction due to a dysregulated host immune response to infection and is a leading cause of mortality in the intensive care unit. Sepsis-induced myocardial dysfunction, also called septic cardiomyopathy, is a common and serious complication in patients with sepsis, which may indicate a bad prognosis. Although efforts have been made to uncover the pathophysiology of septic cardiomyopathy, a number of uncertainties remain. This article sought to review available literature to summarize the existing knowledge on current diagnostic tools and biomarkers, pathogenesis, and treatments for septic cardiomyopathy.